2019
DOI: 10.1111/os.12575
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing Versus Minimally Invasive Plate Osteosynthesis for Distal Tibial Fractures: A Systematic Review and Meta‐Analysis

Abstract: To evaluate the application, safety and efficacy of the patients treated with intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) in distal tibia fractures. Following the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines, we searched databases PubMed, Cochrane library, EMBASE and Web of Science from inception of the database up to 10 October 2018, using the keywords “distal tibia fractures”, “plate”, “intramedullary nailing” and “RCT” to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
4
26
2
2
Order By: Relevance
“…Whether in closed or open fractures, IMN appeared to have a lower incidence of wound complications, but MIPO was recommended for the treatment of distal tibia fractures for its advantage in preventing malunion. 2 Our findings also showed that union, nonunion, and malunion rates were acceptable for both distal and midshaft fractures. Although IMN is very common, plate osteosynthesis outcomes with the MIPO technique are also acceptable with respect to healing rate and time.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Whether in closed or open fractures, IMN appeared to have a lower incidence of wound complications, but MIPO was recommended for the treatment of distal tibia fractures for its advantage in preventing malunion. 2 Our findings also showed that union, nonunion, and malunion rates were acceptable for both distal and midshaft fractures. Although IMN is very common, plate osteosynthesis outcomes with the MIPO technique are also acceptable with respect to healing rate and time.…”
Section: Discussionsupporting
confidence: 70%
“… 1 These fractures can be treated conservatively, or operatively with intramedullary nailing (IMN), plate osteosynthesis, or external fixation depending on the fracture pattern and soft tissues. 2 , 3 Although improvements have been made in intramedullary nails, locking plates, and minimally invasive plate osteosynthesis (MIPO) techniques, no consensus has been achieved on the optimal surgical technique. 4 , 5 IMN has become popular for the treatment of displaced diaphyseal tibia fractures, especially transverse fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Distal-third tibia fractures have been noted with a high rate of complication, and its treatment strategy should be carefully planned. As pointed out by some researchers that intramedullary nailing was associated with more malalignment and anterior knee pain [1][2][3][4], plating seemed to be a simple and effective method for this fracture. To protect the blood supply and provide durable stabilization, the bridge technique with a locking plate by minimally invasive plate osteosynthesis was extensively adopted.…”
mentioning
confidence: 90%
“…However, plate fixation management of these fractures has often resulted in complications such as infections, delayed unions or nonunions, and implant failures [6][7][8]. In recent years, intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) have become common fixation methods for distal tibia fractures [9,10]. Our previous study of a meta-analysis based on 13 randomized controlled trials (RCTs) with 924 patients revealed that IMN for distal tibia fractures is associated with a lower risk of wound complications and a shorter time to union than those for MIPO [11].…”
Section: Introductionmentioning
confidence: 99%